Genetic Variability of Incretin Receptors and Alcohol Dependence: A Pilot Study - Tsermpini, Evangelia Eirini; Goričar, Katja; Kores Plesničar, Blanka; Plemenitaš Ilješ, Anja; Dolžan, Vita (Frontiers in Molecular Neuroscience, 2022)
Alcohol dependence is a chronic mental disorder that leads to decreased quality of life for patients and their relatives and presents a considerable burden to society. Incretin hormones, such as glucose-dependent insulinotropic polypeptide (GIP) and glucagon-like peptide one (GLP-1) are endogenous gut-brain peptides, which can travel across the blood-brain barrier and access the nervous system. Their respective receptors, GIPR and GLP-1R, are expressed in the reward-related brain areas and are involved in memory formation and neurogenesis, which results in behavioral changes in rodent models. The current study investigated the potential association of genetic variability of incretin receptors with alcohol dependence and alcohol-related psychosymptomatology. Alcohol dependence and comorbid psychosymptomatology were assessed in a cohort of Slovenian male participants, comprised of 89 hospitalized alcohol-dependent patients, 98 abstinent alcohol-dependent patients, and 93 healthy blood donors. All participants were genotyped for GIPR rs1800437 and GLP1R rs10305420 and rs6923761 polymorphisms. For the statistical analysis Kruskal-Wall and Mann-Whitney tests were used in additive and dominant genetic models. Our findings indicated that GIPR rs1800437 genotypes were associated with an increased risk of alcohol dependence. Statistically significant association between GIPR rs1800437 GG genotype and Brief Social Phobia Scale scores were observed in the abstinent alcohol-dependent patients, while GLP1R rs6923761 GG genotype was associated with Zung anxiety scores in healthy controls. Our pilot study indicates that GIPR rs1800437 may play some role in susceptibility to alcohol dependence, as well as in alcohol-related psychosymptomatology symptoms. To our knowledge, this is the first study that indicates the involvement of GIPR in alcohol dependence. However, studies with larger cohorts are needed to confirm these preliminary findings.